Expand and renew the gender subjective transformations resulting from the encounter between women - Otth Varnava, Stephanie (Revista Bricolaje, 2019)
Based on a work’s group experience with women, this document will reflect on the (im) possibility of questioning certain social mandates to transform the symbolic ordering of sexual difference. In general terms, the text proposes that certain group’s movements articulated around resistance help to promote the reappropriation of gender and the subjective transformation necessary to resignify the differences between women and men.